Pengaruh Hedonic Lifestyle, Literasi Keuangan dan Sikap Keuangan Terhadap Perilaku Keuangan pada Generasi Z dengan Gender sebagai Variabel Moderasi - Nirmala, Annisa Najla; Agustina, Yuli; Subagyo, Subagyo; Istanti, Lulu Nurul (Jurnal Ekonomi Akuntansi dan Manajemen, 2024)
The evolution of the times necessitate individuals to cultivate prudent financial behavior. It was found that many students in the city of Malang revealed a prevalence of hedonistic lifestyle. Many studens in the city of Malang easily felt FOMO (fears of missing out) about a trend. So, the purpose of this study was to investigate how a hedonic lifestyle, financial literacy, and financial attitudes affect the financial behavior of generation z students in Malang city. The research uses a quantitative approach, focusing on generation z students in Malang city as the population with 210 respondents. The results show that financial behavior is negatively impacted by a hedonic lifestyle, while financial literacy and financial attitudes have a positive influence. However, gender does not have any effect on the relationship between hedonic lifestyle, financial literacy, financial attitudes, and financial behavior. The findings of this study are the financial behavior of students in Malang city can be said to be quite good, but still have a hedon lifestyle, becauda of low self-reliance Keywords: Hedonic Lifestyle, Financial Literacy, Financial Attitudes, Financial Behaviour, Gender